IMPACT OF THE DAYS WITHOUT VAT ESTABLISHED IN COLOMBIA DURING THE YEAR 2020 - Pírela Espina , William; Martínez Ramírez, Marle (Revista Arbitrada Formación Gerencial, 2024)
Given the difficult situation presented during 2020 by the pandemic caused by Covid-19 and which has been affecting the entire population worldwide, having a negative effect on all sectors, the Colombian government has applied measures that seek to promote the reactivation of the productive apparatus of the country. The objective of the work was to analyze the impact of the three (03) days without Sales Tax (VAT) established in Colombia during the year 2020 in the framework of the Covid-19 pandemic. It was a hermeneutical, qualitative and descriptive study, the collection of information was done through documentary observation. The government established this measure in order to reactivate the economy, increase electronic transactions and their use of banking services. The government's strategy served to generate massive sales and agglomeration of people in breach of biosafety regulations. It was concluded that the reactivation of the economy can be achieved with the implementation of sustainable actions over time and not isolated events.